Some Remarks to Behavioral Aspects of Brand Management from the Perspective of Foreign Market - Jana MAJEROVA; Margareta NADANYIOVA; Lubica GAJANOVA (Communications of International Proceedings, 2020)
Aspects related to the country of origin of the brand are traditionally identified with cultural identity, political climate, language, history, landscape relief, economic and technical development, as well as religiosity and population. Based on these elements, the country's image can also be understood as an essential element of a marketing strategy forming a dynamic holistic system, a complex of penetration of business and consumer expectations as well as a holistic attitude construct. Thus, the aim of our paper is to provide a contextually wide introduction into further own research of the phenomenon "national branding" and its incorporation into managerial theory and practice. The paper is divided into two parts. The first part deals with the theoretical background of the topic. Subsequently, in the second part of the paper, own analysis of secondary data is provided. The outcomes of the research and subsequently formulated conclusions provide the understanding of overall complexity of national brand and its incorporation into management processes.
Keywords: Brand; Branding; National Brand; National Branding; Country of Origin; Simon Anholt.